The impact of nordic hamstring exercise and prevention programs on incidence hamstring injury in football players: a systematic review and meta-analysis - Rofiq, R. A. A.; Perdana, S. S.; Azizah, A. N. (Advances in Health Sciences Research, 2023)
Background: Football has a fairly high popularity and is admired by people of various ages. Potential injury in football is rather high because, during the game, each player is required to run at high speed. One of the most common injuries is a hamstring injury. Thus, the purpose of this study is to ascertain whether a program for preventing injuries that includes nordic hamstring exercises affects the frequency of hamstring strains among football players. Method: The search of the articles used four electronic databases (PUBMED, SCOPUS, University of Cambridge, and PEDro) with a publication period of 2008 to 2022. Assessment of study quality used the PEDro scale and meta-analysis used Review Manager 5.4. Results: There were eight articles in the systematic review and seven articles in the meta-analysis. Significant results were obtained with p-value = 0.008 in reducing the hamstring injury rate by administering injury prevention program accompanied by nordic hamstring exercises. Conclusions: The systematic review and meta-analysis revealed that hamstring injuries can be reduced by combining injury prevention with nordic hamstring exercises.